High-Power High-Repetition-Rate Tunable Yellow Light Generation by an Intracavity-Frequency-Doubled Singly Resonant Optical Parametric Oscillator - Bing Sun; Xin Ding; Yuntao Bai; Xuanyi Yu; Yang Liu; Jingbo Wang; Lei Zhao; Tengteng Li; Guoxin Jiang; Peng Lei; Liang Wu; Guizhong Zhang; et al. (IEEE Photonics Journal, 2020)
An efficient intracavity-frequency-doubled singly resonant optical parametric oscillator (SR-OPO), pumped by a high-maturity 532 nm laser, tunable in the yellow wavelength region is demonstrated. An elaborate V-shaped idler cavity design is employed for a potassium titanyl phosphate (KTP) OPO nonlinear crystal to achieve a 5.06 W idler output at 1151.2 nm at a 10 kHz pulse repetition frequency. Using a second KTP crystal to intracavity frequency double the circulating idler wave, a 2.37 W yellow output at 575.6 nm is generated. High optical conversion efficiency (25.4% and 11.2%), 0.5 nm spectral linewidth, and 32 ns pulse duration of the 575.6 nm yellow output are achieved.